"Bigger" or "better": the roles of magnitude and valence in "affective bias". Issue 4 (18th May 2020) - Love, Jack; Robinson, Oliver J.
ABSTRACT: Negative affective biases are thought to be a key symptom driving and upholding many psychiatric disorders. When presented with ambiguous information, anxious individuals, for example, tend to anticipate lower rewards than asymptomatic individuals (Aylward et al., 2019 . Translating a rodent measure of negative bias into humans: the impact of induced anxiety and unmedicated mood and anxiety disorders. Psychological Medicine ). The assumption is that this is because anxious individuals assume "worse" outcomes. However, predictions are often made about high and low rewards, so it is not clear whether the bias is due to the valence (the "worse" option) or just magnitude (the lower number). We therefore explored the roles of valence and magnitude in a translational measure of negative affective bias. We adapted a two-alternative forced choice (2AFC) "reward-reward" task into a "punishment-punishment" paradigm, and followed up with "high reward-high punishment" and "low reward-high punishment" variants. The results from the "punishment-punishment" paradigm – a bias towards higher punishments in healthy controls – suggest that it is outcome magnitude that is important. However, this is qualified by the other variants which indicate that both valence and magnitude are important. Overall, our results temper the assumption that negative affective biases observed in tasks using numeric outcomes are solely as a result of subjective outcome valence.